Skrining Fitokimia Ekstrak Etanol dan Fraksi Daun Ketapang yang Tumbuh di Sekitar Univ. Abdurrab, Pekanbaru - Muhammad Azhari Herli; Isna Wardaniati (LPPM Universitas Abdurrab, 2019)
Traditionally, ketapang plants are widely used by people to treat diseases of the skin such as scabies, ringworm, and other skin diseases caused by bacteria and fungi. Phytochemical screening on ethanol extract and ketapang leaf extract that grows in Pekanbaru City has never been done. The purpose of this study was to identify active compounds in ethanol extract and extract fraction of ketapang leaves that grew in Pekanbaru City. Based on phytochemical screening results, it is known that ethanol extract of ketapang leaves contains alkaloids and flavonoids, in the hexane fraction contains steroids and ethyl acetate fractions contain flavonoids.